Effect of Soil Working Techniques on Biomass Production of Grewia optiva in Degraded Lands - Singh, Charan; Sharma, N. K.; Vishwanatham, M. K.; Joshie, P.; Mohan, S. C. (Indian Forester, 1997)
The present study was carried out under bouldery riverbed lands to study the effect of depth of holes on biomass production and distribution pattern in Grewia optiva. The study indicated that the shallower soil working (50 cm deep) has better rcsponse on total biomass production as compared to deeper soil working (75 and 100 cm). It was recorded that about 1.91 kg leaves and 5.66 kg twigs/tree (average of 4th to 9th year old plantation), can be obtained every year. Among twigs of different categories, the highest quantity was contributed by the twigs of2-5 cm diameter. It was also observed that under degraded lands the biomass production started declining at the early age of rotation.